Dependência do FMI e a transparência fiscal de países: análise sob a ótica da Nova Economia Institucional - Leroy, Rodrigo Silva Diniz (2020)
As a principle for the democratic State’s consolidation, transparency allows citizens to interact and control the politicians. Among transparency perspectives, the budgetary approach, called fiscal transparency, refers to the availability of fiscal and budgetary data from governments, which must be reported with clarity, reliability, frequency, timeliness, and relevance. Within the scope of national governments, we highlight the role of the International Monetary Fund (IMF) in promoting transparency, since they finance public policies of national governments and are responsible for creating norms and standards for fiscal transparency, application, and monitoring of countries’ actions. On the other hand, the literature points out that the adoption of reforms in countries from the initiative of external actors does not work for the real progress of all the policies. Therefore, the aim of this thesis was to analyze the relationship between the IMF's resource dependence and fiscal transparency in democratic countries. We carried out the analyzes from the perspective of the New Institutional Economy, considering that the fiscal transparency’s institutional environment in the countries tends to change in accordance with the commitment assumed before the IMF and the efficiency of its institutions. The thesis is that in addition to the socioeconomic, demographic and political factors already consolidated in the literature, the countries' dependence on the IMF is an important determinant of their level of fiscal transparency, and contractual relations with the Fund tend to promote democratic advances according to the institutional environment of the countries. The theoretical hypothesis is that the dependence on the IMF has different implications for the fiscal transparency of democratic countries, which vary according to their institutional environment. We chose to use quantitative methods, using the techniques of Exploratory Data Analysis, Multiple Linear Regression with panel data, where transparency proxy was the Open Budget Index (OBI), and analysis of the evolution of the variables. The results showed that better rates of fiscal transparency are generally present in developed and richer countries, with parliamentary governments, greater democratic maturity and lower levels of corruption. We found that the level of IMF financing is higher the smaller the budget openness of the 'Developing' countries and that the joint performance of transparency and democracy varies depending on the characteristics of the countries, with a representative number of observations with variations in opposite directions. The IMF's dependency tends to improve countries' levels of fiscal transparency, which does not always result in enough institutional change to promote their democratic strengthening. The inferences of this thesis fill the gap in the literature by concluding that: in order for improvements in the transparency indexes to have effective results in the maturation of democratic institutions, it is important that the performance of the IMF in the countries happens in a combined way with the internal social transformations.